METHODS OF DETERMINING THE PREFERENCE FOR PURPOSES OF THE CONSTRUCTION OF THE COMPUTERISED DECISION SUPPORT SYSTEM - Becker, Aneta; Becker, Jarosław (Metody Ilościowe w Badaniach Ekonomicznych, 2014)
The article presents the functionality of preference modelling for purposes of the multi-methodical, multi-criteria decision analysis implement_x0002_ed in the computerised decision support system. Research results can be con_x0002_sidered through the prism of preference: authoritatively determined by the decision maker or democratically by the group of beneficiaries and from the perspective of scientific views of the council of experts. Preferences in the system can be determined using several different methods.